Dislocation and Strategies for Belonging in Selected Short Stories of Nigerian Migrant Writers (2016)
The dislocation of individuals from homeland and attempts to belong in transnational spaces in contemporary times have become significant aspects of Nigerian migrant prose fiction. This prose fiction has gained prominence following the re-invention of the homeland irrespective of the migrant status of its writers. Studies of these writings have examined the novel genre and the reinvention of socio-political realities, with little attention to the short story genre and its concerns with dislocation and belonging. This study, therefore, examined the creative impulses of five writers for articulating dislocation and how strategies for belonging in transnational spaces in the selected short stories are negotiated. Postcolonial literary theory and aspects of the Freudian Psychoanalytic literary theory were adopted. Thirty three stories were selected from five short story collections based on the writers‘ migrant perspective and significant preoccupation with dislocation and strategies for belonging. The texts were: A Life Elsewhere (ten stories) by Segun Afolabi, Voice of America (six stories) by E. C. Osondu, News from Home (six stories) by Sefi Atta, The Thing around your Neck (six stories) by Chimamanda Adichie and Short Stories (five stories) by Chika Unigwe. The stories were subjected to critical and literary analyses. Migration and its corollaries were significant aspects of these writers‘ creative thrust and sensibilities. Identifiable perspectives that attested to the writers‘ dislocation were prominent in the stories. Dislocation and the strategies adopted in order to belong were projected textually. Thus, the narratives were versatile in oscillating between different locations. Afolabi‘s stories projected a narrative style fixated with conveying the psychological effects of dislocation, and the dilemma of dual consciousness and belongingz that attends this. He emphasised the internal crises of characters by employing the technique of interior monologue. Osondu focalised socio-cultural dislocation and problematised the existential complexities that circumscribe living in Nigeria or the diaspora. His creative strategy sustained dystopic images from Nigeria as a rationale for transnational existence, stereotyping his narrative approach and preoccupation. In Atta‘s narrative approach, survival was imperative. She strategised the survival of her characters and highlighted the human condition in national and transnational territories. However, she maintained a critical stance in interrogating the homeland. Critical socio-cultural realities attested to Unigwe‘s involvement in the re-invented spaces that were negotiated. She explicably mediated the realities of two spaces through the use of juxtaposition, flashback and digression. Adichie problematised the characters‘ perceptions of transnational existence. These stories developed as subtle narratives that emphasised an awareness of the realities she re-invented. Nigerian migrant short stories displayed fluctuating literary focus between homeland and diaspora, and the literary approach of the writers functioned as an imperative for interacting, surviving and belonging in transnational spaces. These stories were critical in understanding transnational interaction and its complex implication in contemporary times